Pertanggungjawaban Hukum Direktur Rumah Sakit Dalam Pelaksanaan Terapi Oksigen Hiperbarik - Siti Hamidah (Jurnal Hukum dan Etika Kesehatan, 2021)
The community's need for quality and affordable health services cannot be delayed any longer and a dynamic and increasingly critical Indonesian society demands sophisticated and humane professional services. The Ministry of Health has a health service policy that is based on the vision of an independent community to live healthily and has a mission to make people healthy. One of the health services that is needed by the community is hyperbaric oxygen therapy, which is a therapy using pure oxygen in a high-pressure room which was originally used as the main treatment for diving diseases, now hyperbaric has also been used as an additional treatment and other treatment options for the general public to help cure various diseases. With the increasing public demand for hyperbaric oxygen therapy services and many hospitals that provide services for this therapy. The government through the Minister of Health needs to issue a Decree of the Minister of Health Number 120 / MENKES / SK / II / 2008 concerning Hyperbaric Medical Service Standards. The establishment of operational standards in the implementation of hyperbaric oxygen therapy is a reference for the responsibility of the Hospital Director as the executor of the therapy service provider.